GEYMIFIKATSIYA: O‘YIN VA TA’LIM O‘RTASIDAGI PSIXOLOGIK KOʻPRIK - Kamalova, G. (SCIENCE and SOCIETY, 2025)
This article analyzes the psychological and pedagogical foundations of applying gamification technologies in the educational process. Gamification is considered an innovative approach that enhances students’ motivation, engagement, and creative thinking by integrating game elements into the learning environment. The study highlights the importance of game mechanics in strengthening intrinsic motivation, ensuring emotional stability, and developing social communication skills among learners
Keywords: gamification; psychological motivation; pedagogical approach; innovative technologies; educational process; game elements; interactive methods